Let the shorter leg have length x.
The longer leg has length x + 2.
The hypotenuse has length x + 4.
Use the Pythagorean Theorem:
x^2 + (x + 2)^2 = (x + 4)^2
x^2 + x^2 + 4x + 4 = x^2 + 8x + 16
2x^2 + 4x + 4 = x^2 + 8x + 16
x^2 - 4x - 12 = 0
(x - 6)(x + 2) = 0
x = 6 or x = -2
A length cannot be negative, so the shorter leg has length 6 cm.
The longer leg has length 8 cm.
The hypotenuse has length 10 cm.
(This is a common Pythagorean triple, by the way, so you could have found the answer like that. :D )
2006-11-25 15:36:24
·
answer #1
·
answered by hokiejthweatt 3
·
1⤊
0⤋
First we would label the shorter leg X. And since the longer leg is 2cm larger tahn the shorter leg, we would lable the longer leg X+2. Since the hypotenuse is 2cm longer than the longer leg, its length would be equal to (X+2)+2 or basically X+4. Then you must use the pythagorean thereom (a squared+bsquared = c squared, where c is the hypotenuse) to create an equation.
So let a=X, let b =X+2, c=X+4
(x)^2+(X+2)^2=(X+4)^2
THat is your equation, and one you factor out the exponents you get:
X^2+X^2+4X+4=X^2+8X+16
now combine like terms:
2X^2+4X+4=X^2+8X+16
next, you want to make the equation equal to zero, so you subtract whats on the right of the equal sign.
X^2-4X-12=0
now you can use the quadratic formula (x=-b+-Sq. root(b^2-4ac)/2a) to find the value of x, (a is 1, b is -4, c is -12)
AFter solving with the formula you should get x to be either 6 or -2 becuase of the plus or minus sign. Since we are dealing with triangles, the length of X must be positive, eliminating -2 as an answer. So X=6. X+2=6+2=8. X+4=6+4=10. You should get 6 for the shorter side, 8 for the longer side, and 10 for the hypotenuse. I hope that helps!
2006-11-25 15:48:24
·
answer #2
·
answered by Gillman Donald 2
·
1⤊
0⤋
Lets call the shortest leg x. Then the longer leg is x+2, and the hypotenuse is x+4.
So x^2 + (x+2)^2 = (x+4)^2, using pythagoras.
Expanding each side:
x^2 + x^2 + 4x + 4 = x^2 + 8x + 16
x^2 - 4x - 12 = 0
(x-6)(x+2) = 0
x = 6 or x =-2
Obviously we can't have side length -2, so x = 6.
So its a 6-8-10 triangle, so the hypotenuse is 10cm.
2006-11-25 15:37:39
·
answer #3
·
answered by stephen m 4
·
1⤊
0⤋
enable us call the size of the hypotenuse h . Then the size of the different unknown area will be ½h subsequently, h² = 7² + (½h)² = 40 9 + ¼h² hence, h² - ¼h² = 40 9 ¾h² = 40 9 h² = 40 9 x 4 ÷ 3 = 196 ÷ 3 h = sq. root of (196 ÷ 3) = 8·0829 (approx. 8·08cm)
2016-11-26 22:22:18
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
let the shorter of the two legs be x cm
longer leg=x+2cm
length of the hypotenuse
=longer leg +2
=x+2+2
=x+4
now applying the Pythagoras theorem
a^2+b^2=c^2
x^2+(x+2)^2=(x+4)^2
x^2+x^2+4x+4=x^2+8x+16
adding -x^2-8x-16
x^2-4x-12=0
(x-6)(x+2)=0
x=6
so thepythagoran triplets are
6,8,10 cm
the length ofthe hypotenuse=10cm
2006-11-25 15:50:56
·
answer #5
·
answered by raj 7
·
1⤊
0⤋
Start out with what you know. c = b +2, b = a + 2, and
c² = a² + b² Substitute
(a+4)² = a² + (a + 2)² so that
a² + 8a + 16 = 2a² + 4a +4 and
a² -4a - 12 = 0
Now solve the quadratic and use the positive root for the length of the smallest leg (a), and calculate b and c from that.
Doug
2006-11-25 15:42:36
·
answer #6
·
answered by doug_donaghue 7
·
1⤊
0⤋
let x=shorter leg
then x+2=longer leg
then x+4=hypotenuse
x^2+(x+2)^2=(X+4)^2
x^2 +x^2 +4x +4=x^2 +8x +16
simplfy..
X^2-4x-12=0
solve for x
(x-6)(x+2)=0
x=6,-2
since distance can't be negative, x=6
so, 6+4=10 is the hypotenuse
2006-11-25 15:42:03
·
answer #7
·
answered by yourdaddy0 2
·
1⤊
0⤋
short is A long is A+2 hypo is A+4 formula is a squared plus b squared equals c squared so its A squared plus (A+2)squared equals (A+4) squared. solve agebraically for A
2006-11-25 15:37:27
·
answer #8
·
answered by David B 6
·
1⤊
0⤋
assume hypotneuse as (x+2)cm, long side as xcm n short side as (x-2)cm
use pythogoreon theorem,
(x+2)(x+2)=(x)(x) X (x-2)(x-2) n solve
then x=0 or 8
therefore hypotneuse=10 since x is unequal to zero.
2006-11-25 15:39:19
·
answer #9
·
answered by muwahhid r 1
·
1⤊
0⤋